Pengaruh Pajak Hotel, Pajak Restoran Dan Pajak Parkir Terhadap Pendapatan Asli Daerah Deli Serdang, Sumatera Utara Periode 2019-2021 - Latersia Br Gurusinga; Thevanni Tri Puspita Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to examine and analyze the effect of hotel tax, restaurant tax and parking tax on local revenue of Deli Serdang, North Sumatra for the 2019-2021 period. The Regional Government of Deli Serdang has lost a lot of Local Original Revenue (PAD) during the current Covid-19 pandemic. This research was conducted in Deli Serdang, North Sumatra for the 2019-2021 period. Researchers obtained research data by entering the site https://bapenda.deliserdangkab.go.id/website/web. The population of this study is hotel tax, restaurant tax, parking tax and local revenue of Deli Serdang, North Sumatra for the 2019-2021 period. The research sample is 3 x 12 data so that 36 data. Data collection techniques are secondary data using documentation techniques. The data analysis technique of this research uses multiple linear regression. The results of this study partially and simultaneously have no effect on Hotel Tax, Restaurant Tax and Parking Tax on Regional Original Revenue of Deli Serdang, North Sumatra for the 2019-2021 period. Keywords: Hotel Tax, Restaurant Tax, Parking Tax, Local Own Revenue